Topical vs Peribulbar Anesthesia: Comparison of Anterior Chamber Depth and the Resultant Visual Outcome After Phacoemulsification - Naik, Mayuresh P (Clin Ophthalmol, 2020)
PURPOSE: To compare anterior chamber depth and postoperative visual outcome in patients undergoing phacoemulsification under topical vs peribulbar anesthesia. MATERIALS AND METHODS: Prospective, randomized, comparative observational study. Group I: Patients undergoing phacoemulsification under topical anesthesia. Group II: Patients undergoing phacoemulsification under peribulbar anesthesia. Once patients were selected, baseline a standard ophthalmic examination was done including best-corrected visual acuity (BCVA), refraction, IOP by NCT, anterior segment evaluation with slit lamp biomicroscopy, keratometry, axial length, and ACD measurement by IOL master. Post-operatively, the patients were reviewed at day 1, week 1, week 6 for the same parameters. Statistics: 1. Quantitative variables: Paired and unpaired t-test. 2. Qualitative variables: Chi square test. A P-value of <0.05 was considered statistically significant. RESULTS: Inter-group comparisons of post-operative change in ACD at 1-week post-op (P-value<0.001) and 6-week post-op (P-value<0.001) were statistically significant when compared to the pre-op values. The mean spherical equivalent in group I was 0.27±0.26 d and that in group II was 1±0.32 d at 1-week post-op. The mean spherical equivalent in group I was 0.23±0.20 d, while that in group II was 0.85±0.64 d at 6-week post-op. This difference was statistically significant both at 1-week post-op (P-value=0.002) and 6-week post-op (P-value<0.001). CONCLUSION: Post-phacoemulsification, the ACD is more after peribulbar anesthesia as compared to topical anesthesia. Post-op refractive outcome is better with the use of topical anesthesia.